2017
DOI: 10.13031/trans.12313
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Parameter Sensitivity and Identifiability of Root Zone Water Quality Model (RZWQM) for Dryland Sugarbeet Modeling

Abstract: ABSTRACT. Sugarbeet is being considered as one of the most viable feedstock alternatives to corn for biofuel production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The crop modeling category includes studies simulating crop growth or yield, either as stand-alone models or as submodels within hydrologic and water quality models. McDaniel et al, 2017aMcDaniel et al, , 2017bMcDaniel et al, , 2017cMittelstet et al, 2017;Muenich et al, 2017;Renkenberger et al, 2017;Wallace et al, 2017 USLE andWEPP Lang et al, 2107;Svendsen et al, 2017;Wu et al, 2017 WEPP andUSLE Grace III, 2017;Lang et al, 2107;Lisenbee et al, 2017;Srivastava et al, 2017;Wang, L. et al, 2017;Wu et al, 2017Crop modeling APSIM Araya et al, 2017Whitbread et al, 2017AquaCrop Espadafor et al, 2017Linker and Kisekka, 2017;Wibowo et al, 2017DSSAT-CSM-CERES-Beet Anar et al, 2017DSSAT-CSM-CERES-Maize DeJonge and Thorp, 2017Fang et al, 2017aFang et al, , 2017bJoshi et al, 2017;Linker and Kisekka, 2017;Marek et al, 2017;Sharda et Anar et al, 2017;Fang et al, 2017aFang et al, , 2017bLinker and Kisekka, 2017;Liu et al, 2017SWAT Feng et al, 2017 feed value but not crude protein.…”
Section: Crop Yields and Water Usementioning
confidence: 99%
“…The crop modeling category includes studies simulating crop growth or yield, either as stand-alone models or as submodels within hydrologic and water quality models. McDaniel et al, 2017aMcDaniel et al, , 2017bMcDaniel et al, , 2017cMittelstet et al, 2017;Muenich et al, 2017;Renkenberger et al, 2017;Wallace et al, 2017 USLE andWEPP Lang et al, 2107;Svendsen et al, 2017;Wu et al, 2017 WEPP andUSLE Grace III, 2017;Lang et al, 2107;Lisenbee et al, 2017;Srivastava et al, 2017;Wang, L. et al, 2017;Wu et al, 2017Crop modeling APSIM Araya et al, 2017Whitbread et al, 2017AquaCrop Espadafor et al, 2017Linker and Kisekka, 2017;Wibowo et al, 2017DSSAT-CSM-CERES-Beet Anar et al, 2017DSSAT-CSM-CERES-Maize DeJonge and Thorp, 2017Fang et al, 2017aFang et al, , 2017bJoshi et al, 2017;Linker and Kisekka, 2017;Marek et al, 2017;Sharda et Anar et al, 2017;Fang et al, 2017aFang et al, , 2017bLinker and Kisekka, 2017;Liu et al, 2017SWAT Feng et al, 2017 feed value but not crude protein.…”
Section: Crop Yields and Water Usementioning
confidence: 99%
“…Two articles in the collection discuss the importance of model parameterization and the need for high-quality experimental data in model calibration and validation: Espadafor et al (2017) and Anar et al (2017). Even for deterministic or process-based models, calibration and validation using high-quality experimental datasets is a basic requirement before the models should be used to assess management strategies.…”
Section: Model Development and Parameterizationmentioning
confidence: 99%
“…Espadafor et al (2017) concluded that their calibrated and validated AquaCrop model can be used for simulation of dry beans in different environments. Anar et al (2017) parameterized, calibrated, and validated the CERES sugarbeet model to simulate the effects of sugarbeet production on soil and water quality in North Dakota. They emphasized the need for sensitivity analysis to identify and determine parameters to which model output was most sensitive.…”
Section: Model Development and Parameterizationmentioning
confidence: 99%